SCHOOL INCLUSION: CHALLENGES AND PATHS TOWARDS EQUITABLE AND QUALITY EDUCATION - Amilton da Costa, José (Revista Gênero e Interdisciplinaridade, 2025)
This paper addresses school inclusion, highlighting its importance in guaranteeing the right to education for individuals with special educational needs. It discusses existing challenges, such as social, pedagogical, and architectural barriers, and emphasizes the need for a shift in paradigms, attitudes, and values ​​in society and in pedagogical practice. It emphasizes that inclusion is not limited to physical integration, but involves a shift in perspective that promotes the participation, autonomy, and citizenship of all students, respecting diversity as a resource. Furthermore, it highlights the role of public policies, legislation, and collective action in building more democratic and accessible schools.